2017
DOI: 10.1002/14651858.cd007387.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal drainage versus no drainage after pelvic lymphadenectomy for the prevention of lymphocyst formation in women with gynaecological malignancies

Abstract: Placement of retroperitoneal tube drains has no benefit in the prevention of lymphocyst formation after pelvic lymphadenectomy in women with gynaecological malignancies. When the pelvic peritoneum is left open, the tube drain placement is associated with a higher risk of short- and long-term symptomatic lymphocyst formation. We found the quality of evidence using the GRADE approach to be moderate to high for most outcomes, except for symptomatic lymphocyst formation at 12 months after surgery, and unclear or l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 23 publications
(37 reference statements)
1
18
0
1
Order By: Relevance
“…Surgical‐site drains are often used with the aim of reducing haematomas and surgical‐site infection. A limited number of robust studies have investigated the effectiveness of drains in preventing postoperative complications, and many did not demonstrate any benefit of drain insertion over no drain. In orthopaedic surgery, conventional suction drains can increase postoperative blood loss.…”
Section: Surgical Strategiesmentioning
confidence: 99%
“…Surgical‐site drains are often used with the aim of reducing haematomas and surgical‐site infection. A limited number of robust studies have investigated the effectiveness of drains in preventing postoperative complications, and many did not demonstrate any benefit of drain insertion over no drain. In orthopaedic surgery, conventional suction drains can increase postoperative blood loss.…”
Section: Surgical Strategiesmentioning
confidence: 99%
“…There is increasing evidence in Cochrane Reviews that routine abdominal drainage a er various abdominal operations is not essential (Cheng 2016;de Jesus 2004;Gurusamy 2007a;Gurusamy 2013;Gurusamy 2007b; Wang 2015). The routine use of surgical drains has been questioned in other areas, including thyroid, gynaecological, and orthopaedic surgeries (Charoenkwan 2017;Gates 2013;Parker 2007;.…”
Section: Agreements and Disagreements With Other Studies Or Reviewsmentioning
confidence: 99%
“…The authors concluded that drainage was not associated with reduced rates of lymphocyst formation. On the contrary, use of surgical drains increased rates of symptomatic lymphocyst formation when the pelvic peritoneum was left open 29 ; a MA reported similar conclusions. 30 In a RCTexamining the use of retroperitoneal drainage after complete paraaortic lymphadenectomy, the authors observed that the drainage group had a higher rate of complications, symptomatic lymphocysts and ascites, and longer hospital stay.…”
Section: B No Routine Peritoneal Drainsmentioning
confidence: 87%